2017
DOI: 10.1002/psc.2993
|View full text |Cite
|
Sign up to set email alerts
|

Bike peptides: a ride through the membrane

Abstract: Several natural peptides have a biaryl or biaryl ether motif in their biologically active structures. A model bicyclic pentapeptide containing a biaryl bridge has been synthesized by solid-phase peptide synthesis combining on-resin Suzuki and Miyaura cross-coupling reactions. Its biological properties in terms of permeability, stability and cytotoxicity have been studied, demonstrating the positive contribution of the biaryl bridge, excellent membrane penetration and serum stability Copyright © 2017 European P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Earlier studies of our group demonstrated that the incorporation of an extra cyclization increases considerably the biostability in human serum. The published results demonstrated outstanding values of protease resistance, which can be quite beneficial.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Earlier studies of our group demonstrated that the incorporation of an extra cyclization increases considerably the biostability in human serum. The published results demonstrated outstanding values of protease resistance, which can be quite beneficial.…”
Section: Resultsmentioning
confidence: 84%
“…The peptide was prepared using the standard methodology of García‐Pindado et al p NZ‐(7Br)Trp‐OH and Fmoc‐(7Br)Trp‐OH were used as the second and fourth amino acids, respectively. The synthesis was performed on solid‐phase using Fmoc/ t Bu chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of bicyclic peptides containing a biaryl bridge and a cyclic backbone was described by García‐Pindado et al. in 2017, in which the cross‐coupling reaction took place between a boronophenylalanine and a iodophenylalanine to generate the biaryl bridge on resin . This approach was extended to bromotryptophan containing peptides in 2018 .…”
Section: Suzuki–miyaura Cross‐couplingmentioning
confidence: 99%
“…The serum stability of the bicyclic tryptophan peptides was not investigated . However, the previous study on a bicyclic peptide with a phenylalanine–phenylalanine biaryl bridge did not show any significant degradation in human serum within 24 h …”
Section: Suzuki–miyaura Cross‐couplingmentioning
confidence: 99%
“…The formation of the biaryl bond has been achieved via a Suzuki-Miyaura cross-coupling reaction, a Pd-catalyzed C-H activation or a Cu-mediated oxidative coupling. The former reaction has allowed the synthesis of peptides containing a Trp-Tyr [4,15], a Phe-Phe [15][16][17][18], a Phe-Tyr [15,17,19] or a Tyr-Tyr [15,[19][20][21] linkage. The C-H activation reaction has been used to form the biaryl bonds Trp-Phe and Trp-Tyr [22,23], while the Cumediated oxidative phenol coupling has provided access to peptides bearing a Tyr-hydroxyphenylglycine motif [24].…”
Section: Introductionmentioning
confidence: 99%